Response of cecropin transgenesis to challenge with Edwardsiella ictaluri in channel catfish Ictalurus punctatus. Issue 126 (July 2022) - Abass, Nermeen Y.; Simora, Rhoda Mae C.; Wang, Jinhai; Li, Shangjia; Xing, De; Coogan, Michael; Johnson, Andrew; Creamer, David; Wang, Xu; Dunham, Rex A.
Abstract: Constructs bearing the cecropin B gene from the moth Hyalophora cecropia, driven by the cytomegalovirus (CMV) promoter, or the common carp beta-actin (β-actin) promoter were transferred to channel catfish, Ictalurus punctatus via electroporation. One F3 channel catﬁsh family transgenic for cecropin transgene driven by the CMV promoter, and one F1 channel catﬁsh family transgenic for cecropin transgene driven by the common carp β-actin promoter were produced. F3 and F1 individuals exhibited enhanced disease resistance when challenged in tanks with Edwardsiella ictaluri, the causative agent of enteric septicemia of catfish (ESC). Inheritance of the transgene by the F1 and F3 generation was 15% and 60%, respectively. Growth rates of the cecropin transgenic and non-transgenic full siblings (controls) channel catfish were not different ( P > 0.05). All transgenic fish showed significant resistance to infection by ESC at day 3 and day 4 post exposure ( P = 0.005). No correlation was detected between body weight and time to death for all genetic groups ( P = 0.34). Results of our study confirmed that genetic enhancement of E. ictaluri resistance can be achieved by cecropin transgenesis in channel catfish. In addition to survival rate, improving survival time is essential because the extension of survival time gives a better chance to apply treatments to stop the bacterial infection. Highlights: Genetic enhancement of E. ictaluri resistance can be achieved by transgenesis. Non-transgenic channel catfish survived less time than cecropin-transgenic. No correlation was detected between weight and time to death for all genotypes.